Sistem Pendukung Keputusan Rekomendasi Penilaian Kinerja Karyawan Untuk Menentukan Status Pemberian Reward Level Operator dan Foreman Menggunakan Metode Adaptive Neuro Fuzzy Inference System (ANFIS) - Sandy Irawan; Judi Prajetno Sugiono (SMATIKA JURNAL : STIKI Informatika Jurnal, 2020)
Employees are required to have a good work ethic to advance their company. This causes many companies to motivate their employees in various ways. The general goal is for better and more stable employee performance so that it benefits the company. Rewards are given to employees who excel and can achieve certain targets, this is more effective in motivating employees than punishment so that it can be a source of motivation for employees to work optimally. In giving rewards, sometimes employees do not match the results of their performance and without applying good calculations. For that, we need a recommendation system to support employee performance appraisal to get rewards. One of the methods used is the Adaptive Neuro-Fuzzy Inference System (ANFIS) method. This method was chosen because it can complete employee performance appraisals based on predetermined criteria and is used as a reference in giving rewards. The amount of data obtained and will be used is several 537employee data which will be divided into two data, namely training data which functions as a model of 524 data, and test data which functions to test the system of 13 data and obtained the model validation calculation value of 0.867189 or 87%.